Makātīb-i ʻAlī va Muʻāviyah : tabṣirah Sharḥ Nahjulbalāgẖah . - Qalbī, Muḥammad Isḥāq (ʻUs̲māniyah Akaiḍmī, 1979)
Critical evaluation of a chapter of Nahjulbalāgẖah, a collection of speeches and letters by ʻAlī ibn Abī Ṭālib, ca. 600-661, 4th caliph of Islam.